(untitled) (The International Journal for Scientific Research, 2024)
The study aimed to identify the reality and future of implementing digital government in the United Arab Emirates, and its role in supporting the country’s economic growth. This is done by learning about the concept of digital government, its elements, and its importance, and then learning about the foundations of implementing digital government in the United Arab Emirates. The role of the digital government in enhancing the position of the United Arab Emirates regionally and internationally as a center for technical progress and e-commerce, and knowing the position of the United Arab Emirates in the relevant global competitiveness indicators through the use of the descriptive analytical approach and the case study approach. The study reached a set of results, the most important of which are: The contribution of the United Arab Emirates’ adoption of modern technology and its application to digital government in achieving the concept of leadership and innovation, and developing distinguished infrastructure, as the country has allocated large investments to support the information technology sector; This led it to become a regional center for information and communication technology services and industry, and created an attractive investment environment in the information technology sector, which enhanced the diversification of sources of income and increased the size of the gross domestic product and its dependence on non-oil sectors, as the percentage of increase in the gross domestic product reached 7.9%. Year 2022, these sectors, of all types, relied on a qualified infrastructure of technical development, which highlights the importance of the state adopting technical progress through digital government in supporting economic growth. Digital transformation in the United Arab Emirates also contributed to enhancing its competitiveness in the international system by occupying first place globally in 23 indicators in 2020 in multiple sectors, including communications, health, work, and residence, all of which fall within the digital transformation in the United Arab Emirates. The study recommended a set of recommendations, including the need to generalize the success of the United Arab Emirates’ experience in implementing the digital government project to Arab countries; this is due to the success of its application in the UAE and its role in facilitating and simplifying all procedures and services provided to customers. Its impact on reducing time and costs, and its role in attracting investments and promoting economic growth. In addition to continuing to build and strengthen the education system using modern technical means, which contributes to spreading the culture of information technology and preparing technically qualified educational personnel to deal with the requirements of technical development.